Process of Passenger Service in the Airport Terminal - Kwasiborska, Anna (Studia Oeconomica Posnaniensia, 2016)
The article presents issues related to passenger clearance in the airport terminal. The process of passenger service affects transport carriers, service located within the airport, the handling agents, and the airport operators. The entire passenger service at the airport is a result of the merger of operations of different companies. An important aspect of passenger service during the process is proceeding according to rules and procedures described in ensuring the highest level of safety. The main aim of this article is to show the wide range of activities during passenger service carried out in the airport terminal.